A Coumarin‐Based Fluorescent Probe for the Detection of Hypochlorite Ions and Its Applications in Test Paper and Cell Imaging. Issue 29 (4th August 2020) - Xie, Ya; Zhou, Cuiping; Zhang, Shiqing; Yan, Liqiang; Wu, Xiongzhi; Shan, Yang
Abstract: A turn on fluorescence probe was designed cleverly and synthesized simply through the condensation reaction between coumarin derivative and barbiturate, for sensitively specific recognition of hypochlorite ion (ClO − ). This probe displayed a transient monitor process (about 5 min) to ClO − in a wide range of pH values (3‐10), and the monitor limit could be estimated as low as 0.73μM. What's more, this probe could perform fluorescence imaging of ClO − in living cells, and make ClO − in aqueous solution appear on the convenient test strip visually. Abstract : A coumarin‐based probe with barbiturate was prepared and characterized. It showed excellent detection performance towards ClO −, such as good specificity, significant turn on fluorescence, a short response time, and a wide pH range as well as a low LOD of 0.73 μM. This probe could be applied to trace handily ClO − in water samples by test paper, and perform fluorescent imaging of ClO − in living cells.